Polymeric Transcatheter Heart Valves - Coetzee, Johan (Division of General Surgery, 2022)
Rheumatic heart disease (RHD) is one of the main causes of heart disease in the emerging world. Once the disease has become symptomatic valve repair or replacement is the only treatment currently available. Commercial bioprosthetic valves (surgical and transcatheter) suffer from calcification and decreased durability, especially when implanted into younger patients, while mechanical surgical valves require life-long anticoagulation. Polymeric transcatheter aortic valve insertion (TAVI) is proposed as a solution to provide long-term durability without the need for anticoagulation. A manufacturing method involving the spray coating of polyurethane solutions onto valve moulds, pre-coating a TAVI stent with a polyurethane of higher durometer, and subsequently spraying the combination of the stent and the mould to form integral attachments of the leaflets, is described. Valves were tested for leaflet thickness distribution, hydrodynamic function and accelerated durability, and subsequently implanted in an acute ovine TAVI model as proof of concept. Effective Orifice Area (EOA) >1.7 cm2, regurgitation < 10% and transvalvular pressure gradient < 10 mmHg were achieved. Leaflet thickness correlated indirectly with the EOA and directly with transvalvular pressure gradient, but not regurgitation. After iterative improvements in the manufacturing process, valves with average thicknesses ranging from 140 to 160 μm showed highest durability (>150 million, and up to 600 million cycles). Surface roughness was reduced by applying a final pure solvent coat. Implanted valves showed good function, with no apparent central or paravalvular regurgitation, perfusion of coronaries, and EOA greater than1.6 cm2. In conclusion, a polymeric TAVI valve made by a new manufacturing method showed durability up to 15 years equivalent in vitro, and good hydrodynamic function in vitro and in vivo. The devices hold many potential advantages in terms of automation and cost of manufacturing, as well as function and longevity.